2023
DOI: 10.1002/chem.202202963
|View full text |Cite
|
Sign up to set email alerts
|

PIDA‐mediated Oxidative Decarboxylation of Oxamic Acids. The Role of Radical Acidity Enhancement.

Abstract: The PIDA-mediated oxidative decarboxylation of oxamic acids in the presence of alcohols is shown to afford the corresponding urethanes under thermal conditions. Computational and experimental mechanistic exploration allows to rationalize the different reactivity of PIDA as compared to related cyclic BI-OAc and highlights the importance of the enhanced acidity of the proton in the carbamoyl radical intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…(acetoxy)benziodoxolone (Bi-OAc) or the commercially available phenyliodine diacetate (PIDA)). Conveniently, we demonstrated that the decarboxylation reaction can be either photo- [46,47] or thermo-initiated [45] under very mild conditions. In the first case, the oxidation is mediated at room temperature by a photocatalyst under visible light or near infrared light (NIR).…”
Section: C) Pu Synthesis Via the Oxidative Decarboxylation Of Polyoxa...mentioning
confidence: 89%
See 3 more Smart Citations
“…(acetoxy)benziodoxolone (Bi-OAc) or the commercially available phenyliodine diacetate (PIDA)). Conveniently, we demonstrated that the decarboxylation reaction can be either photo- [46,47] or thermo-initiated [45] under very mild conditions. In the first case, the oxidation is mediated at room temperature by a photocatalyst under visible light or near infrared light (NIR).…”
Section: C) Pu Synthesis Via the Oxidative Decarboxylation Of Polyoxa...mentioning
confidence: 89%
“…Very recently, we developed metal-free approaches to access isocyanates from oxamic acids. [45][46][47] The methodology is based on the use of hypervalent iodine reagents as lipophilic oxidants (e.g. (acetoxy)benziodoxolone (Bi-OAc) or the commercially available phenyliodine diacetate (PIDA)).…”
Section: C) Pu Synthesis Via the Oxidative Decarboxylation Of Polyoxa...mentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidative decarboxylation of oxamic acids was carried out through photocatalysis, 9,11,12 but also electrochemistry 13 and more recently using hypervalent iodine reagents under thermal conditions. 14 In the search for more benign oxidative conditions, we lately found that cheap iron catalysts could efficiently convert oxamic acids into isocyanates (this work). Iron, being an abundant metal, iron complexes have been extensively studied in the field of photochemistry and photophysics.…”
mentioning
confidence: 96%